Understanding on-time mortgage payment history in the wake of the 2007 financial crisis: an application of the responsible financial actions index - Preece, Gloria Lynn (Kansas State University, 2019)
The purpose of this study was to investigate the determinants that explain and predict an individual’s propensity to perform responsible financial actions and make on-time mortgage payments. The research was guided by Social Cognitive Theory (SCT) (Bandura, 1986) and explored personal factors, environmental influences, and attributes of behavior as co-factors within a combined causal framework. Data for this study came from the publicly available, 2009, 2012, and 2015 National Financial Capability Study (NFCS) datasets. These datasets were selected for the specific questions, timeframe, and richness of the financial information provided by the respondents. Responses for each survey were weighted to be representative of Census distributions according to the American Community Survey (FINRA Investor Education Foundation, 2017). The data are weighted to be representative of each state based on age, gender, ethnicity, and education. The two variables of interest were the responsible financial actions index and mortgage payment history. To isolate the determinants of these two variables more accurately, this research adopted a multi-step approach to the analytical procedure. The analyses began with the construction of the responsible financial actions index – unifying the most fundamental responsible financial actions recommended by financial professionals into a single value. Once confirmed as a valid and reliable measure, the responsible financial actions index was explored empirically as both a dependent variable and a target variable. Further analyses involved the application of the SCT Triadic Model to develop OLS and Multinomial Logistic regression models. Utilizing a series of regression models, this study explored empirically the hypothesized relationships among variables categorized as personal factors, environmental influences, attributes of behavior, and on-time mortgage payment history. When exploring variables to predict the responsible financial actions index, the OLS regression models provided consistent findings when analyzing data from the 2009, 2012, and 2015 surveys. As predicted by the SCT Triadic Model, the following personal factors, age, subjective and objective financial knowledge, financial self-efficacy, and financial risk tolerance were significant across all three survey years. The following environmental influences were significant: income, educational attainment, and marital status. To estimate the odds of paying a mortgage on-time, a series of Multinomial Logistic regression analyses were conducted. When evaluating these results, key findings were identified across all three years of data in two models. Model 1, never late vs. late once, and Model 2, never late vs. late more than once. In Model 1, for all three years, self-efficacy was found to be predictive of on-time mortgage payment history. In Model 2, for all three years, both financial self-efficacy and the financial actions index were found to be predictive of on-time mortgage payment history. These findings contribute to the body of empirical literature related to consumer economics and personal financial planning providing insight and understanding for how financial outcomes can be improved through basic responsible financial actions. This has important implications for financial professionals, counselors, and educators given the applicable value for the responsible financial actions index. For example, these results should encourage educators to work towards identifying new pedagogical approaches for improving financial self-efficacy among students.
Keywords: Mortgage payment history; Responsible financial actions index; Social cognitive theory; Financial self-efficacy; National financial capability study; Triadic reciprocal causation model